Uma arquitetura de aplicação gamificada para o monitoramento e tratamento da doença renal crônica - Silva, Carlos Antonio Fernandes da (2019)
Chronic Kidney Disease (CKD) is characterized by the need for permanent and continuous treatment. Data available in 2017 by the Brazilian Society of Nephrology, the estimated total number of patients undergoing analytical treatment in Brazil, were 126,583. In this context, we address some computational applications focusing on supporting the therapeutic treatment of CKD. However, to date, no software architecture has been found in the literature, considering the various factors that CKD patients may exhibit, seeking a change in the lifestyle of patients by conducting incentives and activities related to the evaluation of nephrologists. Against this background, gamification is a useful tool for providing game mechanisms to encourage patients to adhere to DRC treatment, challenges, and real-world rewards, similar to a digital game. In this paper, a gamified application architecture Project is published focusing on the monitoring and treatment of DRC at different stages. Architectural components were used by an extractive and embedded approach as part of the defined architecture. An architecture assessment was conducted with healthcare professionals and a software developer with a scenario-based approach. An application prototype was implemented using web technologies to present a scenario of using the proposed architecture.